Studying some physical and chemical properties of soils in Cua Tieu river, Tien Giang province - Tran , Thi Tuong Linh; Vo , Thi Thanh Quyen; Pham , Văn Ngot; Quach , Van Toan Em (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This paper reports the results of research on some physical and chemical characteristics of soil in relation to the vegetation of Cua Tieu riverbank in Tien Giang province. There are 6 popular vegetation types: 1) Sonneratia casaeolaris L., 2) Sonneratia casaeolaris L. - Nypa fruticans Wurmb - Avicennia officinalis L. - Kandelia candel L. Druce, 3) Sonneratia casaeolaris L. - Phragmites karka (Retz.) Trin. ex Steud, 4)Phoenix siamensis Miq., 5) Sonneratia casaeolaris L. - Nypa fruticans Wurmb, 6) Nypa fruticans Wurmb. In the mudflats, soils are not mature, and pioneer vegetation species is usually Sonneratia casaeolaris L.. On land accreted for years the soil maturity increases, vegetation species such as Avicennia officinalis L., Kandelia candel L. Druce, Nypa frutiicans Wurmb are present.